Morphological description of the female, pupa, and fourth-instar larva and redescription of the male of culex (melanoconion) aliciae (diptera: culicidae) - Bangher, Debora Natalia (2022)
The female, pupa, and fourth-instar larva of Culex (Melanoconion) aliciae are described for the first time, and the male is redescribed. The cibarium, female and male genitalia, pupa, and fourth-instar larva are illustrated. Information on distribution, bionomics, and taxonomy is also included. Males of Cx. aliciae Duret and Cx. martinezi Casal & Garcia are indistinguishable, except for the appearance of the ninth tergal lobes. The female of Culex martinezi has not been described before. The females of Culex aliciae can be recognized by characteristics of the occipital scales, cibarium, and genitalia. The larva of Cx. aliciae and Cx. martinezi can be distinguished from characters of the thorax and abdomen.